Assessing physical activity/behavior of adolescents living in the Pacific with accelerometer data: 231 GENEActiv records in New CaledoniaZenodoZenodoZenodoZenodoZenodoZenodoZenodo - Guillaume Wattelez; Stéphane Frayon; Olivier Galy (Data in Brief)
This paper presents a dataset related to the physical activity behavior of 206 adolescents (107 females and 99 males) from 11 to 16 years old and 25 adults (13 females and 12 males) living in rural (77 adolescents and 15 adults) and urban (129 adolescents and 10 adults) parts of New Caledonia, an archipelago of the South Pacific. Physical behavior was assessed through 60-Hz triaxial GENEActiv accelerometers worn for 5 to 7 consecutive days between July 2018 and April 2019. Participants were randomly recruited at school and trained staff fitted the devices on the nondominant wrist, at which time all were reminded of the expectations while wearing the device.The dataset contains restricted raw .bin accelerometer data provided by the GENEActiv software and open 1-second epoch .csv accelerometer data derived from the .bin files with an R script, provided in the repositories as well. Similarly, there is open information (age range and sex) and restricted information (age in months, place of living, declared cultural community and socioeconomic status) about the participants.The paper describes the file contents, describes the participants involved when collecting this dataset, and gives examples of how the data can be processed to assess the physical behavior of these participants.This high-quality dataset contains diverse sociodemographic information about the participants, which will enable the determination of correlations with their physical behavior. Moreover, since raw data with high granularity and continuous information is provided, studies interested in data processing and testing new methods on time series analyses can use the dataset.